Correction: Evaluating Subcriticality during the Ebola Epidemic in West Africa. - Wayne T A Enanoria; Lee Worden; Fengchen Liu; Daozhou Gao; Sarah Ackley; James Scott; Michael Deiner; Ernest Mwebaze; Wui Ip; Thomas M Lietman; Travis C Porco (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0140651.].